Life connections : pioneers in ecology - Leuzzi, Linda (New York, N.Y. : Franklin Watts, 2000)
Profiles eight scientists whose work shaped the development of ecology as a field of study, including Alexander von Humboldt, E. Lucy Braun, Aldo Leopold, and Sherry Rowland.
Includes bibliographical references (p. 121-123) and index.
Booklist.
Books for the Teen Age (NYPL).
Wilson's Senior High School.
Young Adult
Keywords: Ecologists -- Biography -- Juvenile literature; Ecologists; Ecologists -- Biography